2020
DOI: 10.1093/ckj/sfaa098
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access cannulation and haemostasis: a national observational study of French practices

Abstract: Background We report the results of an observational study of arteriovenous fistula (AVF) cannulation and haemostasis practices in France. Methods The study (sponsored by Brothier Pharmaceutical Inc.) was conducted in 150 dialysis units. Data obtained from 150 supervisory nurses, 1538 nurses and 3588 patients with an AVF were analysed. Results The nurses repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…One study [ 24 ] evaluated practices of hemodialysis nurses in France in responding to post-cannulation bleeding for over 3000 patients. Nurses reported using at least 10 different dressing types, and mechanical compression devices (bracelets, clips or tourniquets) were commonly used for both short and long bleeding times (12.7% and 13.2%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 24 ] evaluated practices of hemodialysis nurses in France in responding to post-cannulation bleeding for over 3000 patients. Nurses reported using at least 10 different dressing types, and mechanical compression devices (bracelets, clips or tourniquets) were commonly used for both short and long bleeding times (12.7% and 13.2%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Sallee et al, it was reported that 56% of the patients had AVF BU needle punctures and 48% of the patients had bled at the puncture sites for more than 10 minutes, however, the relationship between bleeding time and needle bevel position was not discussed [21]. In the previously mentioned study by Gaspar et al, 17 patients were recruited, and it was reported that bleeding was detected in only 27 (3.6%) punctures after a total of 748 punctures.…”
Section: Discussionmentioning
confidence: 99%
“…US guidelines advise against buttonhole (constant site) cannulation owing to reports of increased risk of S aureus infections. 7 However, the technique is still preferred by many patients, 24 , 25 , 26 and the European and British guidelines rather focus on the advice to reduce the infection problem because the data on infectious risk have varied greatly. 6 , 27 We, therefore, studied how to further improve the technique as this could reduce patient discomfort and potentially also reduce the infection risk.…”
Section: Discussionmentioning
confidence: 99%